Increase in FoxP3, CD56 immune cells and decrease in glands PGRMC1 expression in the endometrium are associated with recurrent miscarriages. (February 2020) - Lyzikova, Yulia Anatolievna; Zinovkin, Dmitry Aleksandrovich; Pranjol, Md Zahidul Islam
Abstract: Objective: Recurrent miscarriage (RM) is a multifactorial condition that involves frequent uterine anatomical abnormalities, parental karyotype abnormalities, and clotting disorders. We investigate the potential roles of endometrium FoxP3 + Tregs and CD56+ cells (uNK cells) and endometrial expression of PGRMC1 in the development of recurrent miscarriage. Study design: This prospective study included 102 out of 286 cases of SA patients. The cases were divided into groups with RM (+RM) and without RM (-RM). Immunohistochemistry staining was made using primary antibodies to FoxP3, CD56, and PGRMC1 in both groups. Morphometry analyses were carried out in 10 non-overlapping high power fields. Mann-Whitney U test, Fisher two-tail test, correlation analysis and relative risk (RR) were evaluated. A p < 0.05 was considered statistically significant. Results: An increased presence of CD56-positive (p < 0.001) and FoxP3 + Treg (p = 0.0005) cells was found in the endometrium, with a reduction in PGRMC1 expression compared with -RM group (p = 0.004). A positive correlation was shown between the number of CD56-positive cells and FoxP3 + cells (r = 0.55), and an inverse correlation with PGRMC1 (r =  -0.35) in the + RM group. A similar observation was found in the -RM group, with a positive correlation of uNK cell number with the number of pregnancies (p < 0.001; r = 0.34). Endometrial infiltration of CD56-positive (p < 0.0001) and FoxP3 + (p < 0.0001) cells revealed an increased relative risk of RM. This increased risk was also revealed in SA with a loss of PGRMC1 expression (p < 0.0001). Conclusion: Our prospective study suggests, for the first time, that increased endometrial infiltration of uNK, FoxP3 + Treg cells and a decreased PGRMC1 expression may play potential roles in the development of RM.